VALIDITY OF HYSTEROSCOPY AND HISTOPATHOLOGY IN PATIENTS WITH MENSTRUAL IRREGULARITY - Fakhar, Shazia; Mahmud, Ghazala (Journal of Ayub Medical College Abbottabad, 2010)
Background: Abnormalities in menstrual cycle is the most common presenting symptom in Gynaecology out-patient. Dilatation and curettage has been the diagnostic investigation of choice for decades in such cases. With the advent of new more valid and safe methods, it has been replaced by hysteroscopy as gold standard. The objective of this study was to know the sensitivity and specificity of hysteroscopy in patients presenting with menstrual irregularity. Methods: Validity study was conducted over 269 cases for a period of two years at Maternal and child health centre, Pakistan Institute of Medical Sciences, Islamabad. Inclusion criteria were age ‰¥35 years and abnormal uterine bleeding. Patient with positive pregnancy test, recent cervicitis, vaginitis, endometritis, pelvic infection were excluded. Hysteroscopy and curettage was performed after taking informed consent, mostly on outpatient basis. A predesigned Performa was used for a detailed record of hysteroscopic findings, which were later compared with histopathology report. Data was analysed using MS Excel, and Cross Tabulation was done using Epi-info. Sensitivity, specificity, positive predictive value and negative predictive value of hysteroscopy was calculated against histopathology, the gold standard. Results: Sensitivity, specificity, positive predictive value and negative predictive value of hysteroscopy was calculated against histopathology after excluding 46 (17.1%) cases of uterine fibroid that were diagnosed only at hysteroscopy. Hysteroscopy has shown highest sensitivity for retained products of conception and adenocarcinoma (100%) while a specificity of 90% and above for all hysteroscopic findings. Seventy eight percent of the procedures were performed on outpatient basis, 95% under intravenous sedation and 95% with no operative complication. Conclusion: Hysteroscopy should be used as an adjunct procedure to curettage as it is a better tool for diagnosis of intracavity lesions, with a high sensitivity and specificity for endometrial carcinoma. Keywords: Hysteroscopy, histopathology, menstrual irregularity